Marketing Strategies as Correlates of Sports Talent Development in South West Nigerian Universities - Adande , Abdulazeez Dotu; Setonji, Noel; Omoniyi, Sandra; Onifade , Olufemi (FKIP - Universitas Riau, 2025)
The study investigated marketing strategies as correlates of sports talent development in South West Nigerian Universities. A descriptive research design was adopted to obtain comprehensive information. The population consisted of student-athletes, sports coaches, athletic trainers, and sports directors, with a sample size of 500 respondents selected through simple random sampling. Data was collected using a self-developed Management, Strategies, and Sports Talent Development Questionnaire (MSSTDQ) via Google Forms. Findings revealed that celebrity endorsement, sports promotion, and advertisement significantly influence sports talent development. Based on these findings, it is recommended that universities collaborate with brands to promote sports talents and events, use storytelling techniques to create compelling content, host engaging events to build brand loyalty, and ultimately ensure the long-term success of sports talent development in South West Nigerian universities. It was recommended that sports organisations collaborate with corporate brands such as sports apparel companies or sports equipment manufacturers to promote sports talent and events.